RESOLUTION OF CYSTIC MACROPROLACTINOMA WITH DOPAMINE AGONIST THERAPY - Goh, Qing Ci; Loh, Yee Wen; Ng, Yong Siang; Mak, Woh Wei; Krishnan, Gayathri Devi; Ng, Yoke Mui; Redzuan, Shazatul Reza Mohd; Rajoo, Subashini; Bidin, Mohamed Badrulnizam Long (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Cystic prolactinomas are prolactinomas that harbor cystic regions, usually occupying ≥50% of the tumour volume. It is hypothesized that dopamine agonists are ineffective in reducing cystic tumour mass due to the absence of dopamine receptors in the cystic portion of the tumour. We present a case of a patient with a cystic prolactinoma for which the cyst disappears following treatment with dopamine agonist. CASE A 23-year-old Malay female first presented with secondary amenorrhoea. She attained menarche at 15 years of age and had regular menses since then until 2019. She is otherwise well with no galactorrhoea, headache or visual deficit. The hormonal evaluation revealed hyperprolactinemia (11,131 mIU/L) and hypogonadotropic hypogonadism (estradiol: 64.9 pmol/L, FSH: 7.2 mIU/L). Magnetic resonance imaging (MRI) demonstrated a cystic lesion occupying the pituitary fossa and extending into the suprasellar region; likely Rathke’s cleft cyst with possible concomitant presence of pituitary adenoma. The lesion is abutting the optic chiasm with a height of 15.8 mm. She was treated with cabergoline 0.5mg twice per week. Her prolactin level normalized 3 months later with the resumption of a normal menstrual cycle. However, she defaulted to subsequent follow-up for 1 year before presenting to the endocrine clinic again for galactorrhoea and irregular menstruation. Prolactin level was 2,861 mIU/L. Cabergoline was re-initiated at 0.5 mg twice per week and her symptoms resolved 6 months later with the prolactin level of 311 mIU/L. Repeat MRI showed a right pituitary gland lesion measuring 0.4 x 0.3 x 0.3 cm with no cystic lesion identified. CONCLUSION Initial management strategies for cystic prolactinomas have been debated. In a recent review of cystic prolactinoma patients, 80% with compression of the optic chiasm evident on MRI (mostly without visual field defect) at presentation achieved resolution of chiasm compression with medical treatment. This case highlighted the effectiveness of cabergoline in treating cystic prolactinomas.